PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE THE POWER OF TWO DISERTAI LEBARAN KEGIATAN SISWA (LKS) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IX SMPN 2 DUA KOTO KABUPATEN PASAMAN - Dahlia, Dahlia; Aima, Zulfitri; Pratiwi, Merina (Pendidikan Matematika, 2013)
The Background of this research was the comprehension of mathematical concepts. This research therefore aims to determine how studentsâ learning activities with the implementation of active learning strategy TheÂ  Power Of Two with student work sheet types and to determine whether student comprehension of mathematical concept by applying active learning strategy types The Power Of Two was better than the student comprehension of mathematis concepts with the application of learning conventional class IX student of SMPN 2 Dua Koto. This type of research was experimental research. Population in this research is class IX student of SMPN 2 Dua Koto consisting of three classes. TheÂ  sampling technique is done randomly, which was selected as the sample classes are class IX 3 as the experiments class and class IX 1 as the control class. The instrument used in this final test with indicator of comprehension the concept. Form of test used wasÂ  a form of essay with a reliability test was 0,709. Hypothesis testing use a t-test with the Â of the software MINITAB. Based on the analysis of the data found P-value was less than , then this hypothesis is accepted. Thus concluded that the student comprehension of mathematical concept with application of active learning strategy types The Power Of Two with student work sheet was better than the student comprehension of mathematis concept with coventional learning in class IX SMPN 2 Dua Koto Kabupaten Pasaman.